University Credits as a Measure of Teachers’ Pre-service and In-Service Training: A Longitudinal Approach Using Swedish Data - Johansson, Stefan; Hansson, Åse; Alatalo, Tarja (Frontiers in Psychology, 2022)
In this study, we accessed information about the university credits of all teachers born after 1971 in Sweden as a means of ascertaining the development of their subject knowledge. We examined the university credits they earned during pre-service and in-service training. Data comes from registers Gothenburg Educational Longitudinal Database (GOLD) and the teacher register. We linked GOLD to the teacher register in order to describe the knowledge development of teachers in compulsory school 1998 ̶ 2014. Special focus was on Swedish language and mathematics. Multiple regression and longitudinal modelling were used as our main methods. Results show an increase in pre-service credits during the time period and more credits in Swedish language than in mathematics. To analyze teachers’ in-service training, we followed the development of their university credits over time. Teachers with higher prerequisites in terms of grade point average tended to gain more credits in-service. The study included discussions on ideas and the implications for future research.